Shear strengthening of reinforced concrete T-beams with anchored and non-anchored CFRP fabrics. (May 2022) - Arslan, Musa Hakan; Yazman, Şakir; Hamad, Ahmed Abed; Aksoylu, Ceyhun; Özkılıç, Yasin Onuralp; Gemi, Lokman
Abstract: Strengthening of shear deficient T-beams is not as easy as rectangular beams due to the presence of slabs. In this study, externally bonded reinforcement (EBR) such type of reinforced concrete shear deficient T-beams with and without anchorage in different CFRP configurations was experimentally and analytically investigated. Pursuant to this goal, nine half-scale T-beams were produced and tested with monotonic loading under four points. Seven of these T-beams are strengthened with partial CFRP strip and one is strengthened with full CFRP wrapped in the shear span. The failures of strengthened beams are initiated with the debonding failure of FRP sheets followed by brittle shear failure. In order to prevent this failure, two specimens with partial CFRP strip are fixed to the beam by using anchors at different angles of 45° and 90°. The experimental results indicated that the contribution of EBR to the shear capacity is significant and depends on different variables such as anchorage angle, strengthening type. Moreover, the strengthening method that gives the most effective results in strengthening T-beams are full wrapping CFRP and partial CFRP with a 45-degree anchorage type. The anchorage application increased the shear capacity by 42.6%∼53.8% compared to the reference specimens. In addition, the anchors with angle of 45° increased stiffness by 37%. In terms of ductility, the best result was given by the type of strengthening where the slabs were broken and the beam was completely wrapped. This method contributed 42%∼80% more to ductility than other methods. The obtained experimental results were also compared with the empirical correlations given by ACI 440.2R-17, TBEC-2019 and FIB-2010 and recommendations are given. Especially in fully wrapped beams, the estimation of ACI was determined to be 96%. The estimations of the other codes are far from meeting the experimental results; therefore, essential improvements should be applied to the codes, especially with regard to CFRP deformation and approaches for anchored connections.